Chairside CAD/CAM Materials: Current Trends of Clinical Uses - Giulio Marchesi (MDPI AG, 2021)
Restorative materials are experiencing an extensive upgrade thanks to the use of chairside Computer-aided design/computer-assisted manufacturing (CAD/CAM) restorations. Therefore, due to the variety offered in the market, choosing the best material could be puzzling for the practitioner. The clinical outcome of the restoration is influenced mainly by the material and its handling than by the fabrication process (i.e., CAD/CAM). Information on the restorative materials performances can be difficult to gather and compare. The aim of this article is to provide an overview of chairside CAD/CAM materials, their classification, and clinically relevant aspects that enable the reader to select the most appropriate material for predictable success.